Grade 7 learners' self-configuration experiences within the teacher-learner relationship - Du Plessis, Georgina (My University, 2014)
Humans are relational beings, as they are constantly in interaction with others and with their environment. In schools, learners spend at least nine years of their lives in formal schooling, and the relationships they have with their teachers are bound to have an impact on their self-configuration. According to the Field theory, the Bioecological theory and the Dialogical theory of self, which were used as theoretical frameworks for this study, individuals' self-configuration is impacted by their environment, experiences and interactions with others. The focus of this study was on Grade 7 learners' self-configuration experiences within the teacher-learner relationship. Grade 7 learners are at the beginning of the adolescent phase, which is characterised by many changes, transitions, challenges and uncertainties. One of these transitions is the forthcoming transition from primary school to high school and a healthy self-configuration could assist learners to adapt to these changes in a positive manner. The research was qualitative in nature and made use of the case study method. This allowed the researcher to use data gathering approaches through which the subjective experiences of the participants could be explored. Twelve participants volunteered to take part in this study, and data was gathered by means of individual interviews as well as group discussions. All interviews and group discussions were voice and video recorded, where after they were transcribed and analysed by means of thematic analysis. The analysis allowed for data to be organised into meaningful themes. It was found that learners' experiences of relationships with teachers are both positive and negative. Self-regulation in learners takes place through encouragement and disapproval from teachers, as well as through lessons learnt from teachers and from past experiences. Further studies around self-configuration and teacher-learner relationships are recommended, in order to make teachers more aware of the importance of the teacher-learner relationship, and also to determine what the obstacles are in developing supportive and caring teacher-learner relationships. By highlighting the importance, and by determining the obstacles, more meaningful teacher-learner relationships could be encouraged and developed in order to enhance learners' self-configuration experiences.
MA (Psychology), North-West University, Potchefstroom Campus, 2015
Keywords: Relationships; Teacher-learner relationship; Adolescents; Sense of self; Self-configuration; Field theory; Bioecological theory; Dialogical theory of self